Randomized two way crossover open label study to compare the bioequivalence of LOSARDIL 100 TM (Drug International Ltd, Bangladesh) and COZAAR TM (Merck Sharp & Dhome Ltd, UK) in Bangladeshi normal male volunteers - Sarker, Uttam Kumar; Farhana, Fatiha; Islam, Atikul; Misbahuddin, Mir; Islam, Md. Rabiul (Asian Journal of Pharmaceutical Research and Development, 2023)
Objectives: A crossover-randomized bioequivalence study of two oral formulations of losartan (100 mg) tablets was carried out in 16 healthy male Bangladeshi volunteers. The test and reference formulations were LOSARDIL 100™ (Drug International Ltd, Bangladesh) and COZAAR™ (Merck Sharp & Dohme Ltd, UK), respectively. Methods: Each tablet was administered with 150 mL of water to subjects after whole night fasting condition on two therapy days distinct by 1 week washout period. After administration, blood samples were accumulated periodically for 24 hours. The plasma concentrations of losartan were evaluated using a validated HPLC method. The pharmacokinetic parameters Cmax, Tmax, AUC0→24h, t1/2, and Kel were determined. Results: The mean (± SD) AUC0→24h for losartan of test drug LOSARDIL 100TM for 16 volunteers was 3310 ± 1165 ng.hr/mL whereas it was 3545 ± 1251 ng.hr/mL for losartan of COZAARTM . The relative bioavailability (LOSARDIL 100TM/COZAARTM ratio) was 93%. The Cmax, tmax, half-life of elimination (t1/2) and the rate of elimination (Kel) of losartan of test drug were 1855 ± 675 ng/mL, 0.77 ± 0.39 hours, 4.69 ± 1.17 hour and 0.15 ± 0.04 respectively. The Cmax, tmax, half-life of elimination (t1/2) and the rate of elimination (Kel) of losartan of reference drug were 2254 ± 944 ng/mL, 0.87 ± 0.29 hours, 4.13 ± 1.41 hour and 0.20 ± 0.04 respectively. Conclusion: Depend on the statistical interpretation the 90% CI for the test and reference drugs were observed within the acceptance range of 80-125%. In conjecture, LOSARDIL 100™ is bioequivalent to COZAAR ™ in terms of absorption.